The Adhesion of CrN Thin Films Deposited on Modified 42CrMo4 Steel - O. Lupicka; B. Warcholinski (Advances in Materials Science and Engineering)
Here, the effect of adhesion of CrN hard coatings on modified 42CrMo4 steel substrate is presented. Modifications of the substrate are shot peening, nitriding, shot peening, and nitriding joined process. In the shot peening process, two variable process parameters were used: exposure time (t) and air pressure (p). The nitriding process was conducted in the following parameters: nitriding potential Np = 4.86, nitriding time tn = 3 h, and temperature process T = 530°C. Modified substrates were characterized by surface hardness HV5 and hardness profiles on the cross section of samples and by surface roughness parameters. On such prepared substrates, the CrN coating was deposited. The adhesion of CrN coating on modified substrates was defined by the scratch test. Chemical and phase composition of the films was determined using EDS method and X-ray diffraction, respectively. The surface hardness of deposited films was also defined. The substrate of 42CrMo4 steel without mechanical and heat treatment coated by hard CrN film was used as a reference.